Koalisi Partai Politik Islam Pada PILPRES 2019: Antara Ideologis dan Pragmatis - Addiansyah, M. Nur Rofiq (State Islamic Institute of Kudus (IAIN Kudus), 2019)
This paper will discuss about how coalition forms are carried out by political parties, especially islamic political parties. What is the coalition process, what are the motives of the coalition, and how the formation of the coalition formed will be discussed in this paper. During the Presidential and Vice President Elections in 2019, there were two candidate pairs competing, namely the Ir.Joko Widodo-KH.Maruf Amin and the couple Prabowo Subianto-Sandiaga Salahuddin Uno.This paper uses a qualitative method with the type of case study. The electoral realm of the 2019 Presidential Elections became the empirical space discussed. The 2019 presidential election was supported by a large coalition of Jokowi-Maruf supporters and Prabowo-Sandi suppoters. These two pairs of candidates are supported by political parties based on the Islamic and nationally voters. From this 2019 Presidential Election, we can see the ideological movements of political parties in Indonesia. First, political parties are still oriented towards victory rather than ideology and policy. Second, the ideology of political parties is increasingly blurred. Third, the influence of the electoral system which led to the escape of the ideology of political parties.